Influence of hemodialysis on the plasma concentration of adenosine deaminase in patients with chronic kidney disease - Eduardo O. Chielle; Kaue A. Rigon; Idania A. Arcari; Vanessa Stein; Gelson Antônio dos Santos (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT Introduction: Over the past years there has been a significant increase in hospitalizations and treatments due to kidney complications that eventually resulted in the increased number of patients on dialysis. The adenosine deaminase (ADA) enzyme mediates the formation of some defense cells of the organism and is therefore a marker of inflammation. Objective: The objective of this study was to evaluate biomarkers of renal function and serum ADA of hemodialysis patients. Materials and methods: Blood samples were collected from 80 patients - 40 women and 40 men - between 19 and 60 years old, before and after the completion of hemodialysis. Results: There was a significant difference in levels of creatinine, urea and ADA in pre- and post-hemodialysis periods (p < 0.0001). There was a significant increase in post-dialysis ADA regardless of sex; however there was a significantly greater increase in men. Conclusion: The results showed a reduction in urea and creatinine parameters, evidencing the main purpose of hemodialysis. This study suggests that the determination of ADA activity could be used to monitor inflammation in hemodialysis patients, however wider and more specific studies are needed to show the effectiveness of serum ADA activity as an inflammatory marker in patients with chronic kidney disease.